2019
DOI: 10.3389/fnint.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Brain Network Dysfunctions Associated With Visuomotor Impairments in Autism Spectrum Disorder

Abstract: Background: Individuals with autism spectrum disorder (ASD) show elevated levels of motor variability that are associated with clinical outcomes. Cortical–cerebellar networks involved in visuomotor control have been implicated in postmortem and anatomical imaging studies of ASD. However, the extent to which these networks show intrinsic functional alterations in patients, and the relationship between intrinsic functional properties of cortical–cerebellar networks and visuomotor impairments in ASD ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 91 publications
(138 reference statements)
7
30
0
Order By: Relevance
“…Whilst we do not report neurobehavioural data, one can speculate that the specificity in feedforward and feedbackbased differences might (in part) be related to the cerebellum and basal ganglia [Doyon et al, 2009;Shadmehr & Krakauer, 2008]. fMRI data ] collected whilst executing a motor control task (i.e., the PANESS task) showed that autistic individuals exhibited decreased cerebellar activity, and increased pre-motor cortex activity, compared to controls (see also Wang et al, 2019). This is perhaps not surprising given the well-reported structural (e.g., lower Purkinje cell count, Ritvo et al, 1986;hypoplasia, Courchesne, Yeung-Courchesne, Hesselink, & Jernigan, 1988) and functional (e.g., greater spatial extent and magnitude of activation in ipsilateral anterior cerebellum; Allen et al, 2004] differences found in the autistic cerebellum (see Amaral, Schumann, & Nordahl, 2008;Oldehinkel et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Whilst we do not report neurobehavioural data, one can speculate that the specificity in feedforward and feedbackbased differences might (in part) be related to the cerebellum and basal ganglia [Doyon et al, 2009;Shadmehr & Krakauer, 2008]. fMRI data ] collected whilst executing a motor control task (i.e., the PANESS task) showed that autistic individuals exhibited decreased cerebellar activity, and increased pre-motor cortex activity, compared to controls (see also Wang et al, 2019). This is perhaps not surprising given the well-reported structural (e.g., lower Purkinje cell count, Ritvo et al, 1986;hypoplasia, Courchesne, Yeung-Courchesne, Hesselink, & Jernigan, 1988) and functional (e.g., greater spatial extent and magnitude of activation in ipsilateral anterior cerebellum; Allen et al, 2004] differences found in the autistic cerebellum (see Amaral, Schumann, & Nordahl, 2008;Oldehinkel et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Supporting the hypothesis that low‐frequency force oscillations originate from higher‐level cortical regions, Lodha et al [2013] showed that visuomotor grip‐force oscillations in stroke patients contain increased low‐frequency power <0.5 Hz in their paretic versus non‐paretic hand, whereas controls showed no differences in low‐frequency force oscillations <0.5 Hz between hands [Lodha et al, 2013]. Furthermore, Wang et al [2019] showed that low‐frequency oscillations within the visuomotor network was associated with increased force variability in individuals with ASD. Therefore, low‐frequency force oscillations may be associated with low‐frequency fluctuations of activity in visuomotor brain regions activated during grip‐force tracking.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies show that static force oscillations below 0.5 Hz originate from higher centers [Lodha, Misra, Coombes, Christou, & Cauraugh, 2013], are associated with increased variability of force output during visuomotor grip‐force tracking tasks [Lodha & Christou, 2017; Moon et al, 2014; Park, Kim, Yacoubi, & Christou, 2019], and are amplified when visual feedback error is removed [Fox et al, 2013]. Increased force oscillations below 0.5 Hz during a grip‐force task may reflect deficits within the visuomotor network [Wang et al, 2019] that may also be associated with force tracking accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…。例如, 当研究者把一项社会性决 策任务命名为"社区游戏"时, 与"华尔街游戏" 这个 名称相比, 被试的合作程度会显著提高 (Liberman et al, 2004) (Takeuchi et al, 2012;Zeng et al, 2012; 江琦 等, 2018)。 静息态时的功能连接模式与 任务态时的激活模式相似度近 80% (Biswal et al, 1995;Cole et al, 2016)。值得注意的是, 静息态功 能连接不仅被用来探索感知觉 (Lewis et al, 2009;Taubert et al, 2011), 注意等认知功能上的个体差 异 (Mennes et al, 2010;Posner et al, 2014), 还被用 (Biswal et al, 1995;Fox et al, 2005); 且不同脑区之间的功能连接强度 及连接模式与健康个体的认知能力 (Lewis et al, 2009)及社会性特征 (Nostro et al, 2018;Wang et al, 2019) participants to make a tradeoff between economic benefits and the feelings of others; when participants showed a stronger preference for income maximization, the probability for their partners to receive a painful electrical shock would increase proportionally. This decision was described as either a "harm" to, or simply "not helping" other persons in two frame conditions.…”
mentioning
confidence: 99%